An investigation into control mechanisms of driving performance : resource depletion and effort-regulation - Louw, Tyron Linton (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2013)
Driver fatigue is a complex phenomenon that has a range of causal factors including sleeprelated and task-related factors. These manifest as different safety and performance outcomes. Extensive research has been applied to linking these factors to performance impairment. However, little research focuses on the mechanisms by which this link exists. This research project therefore focuses on the processes underlying how driving performance is controlled and maintained during the development on non-sleep-related driver fatigue. The main aim was to establish whether progressive impairment of driving control over a prolonged drive could be attributed to a depletion of attentional resources, as proposed by Resource Theory, or to a withdrawal of effort, as proposed by Effort-Regulation Theory. As a multicomponent skill, driving requires perception, cognition and motor output. The secondary aim of this research was therefore to assess whether a prolonged drive impairs stage-specific information processing. Participants (n=24) in three experimental groups performed a 90-minute simulated drive wherein they were expected to keep the bonnet of a car on a lane (tracking task). The three groups differed in terms of lane width: small, medium and large, corresponding to low, medium, and high task-demand, respectively. To assess the impacts of this task on stagespecific information processing, participants performed a set of resource specific tests before and after the prolonged drive. Each task had two difficulty variations to ensure that performance decrement was due not only to the task-characteristic, but specifically to resource depletion. The tests probing information processing were: a modified Fitts' tapping task for motor programming, a digit recall task for perception, and an object recognition reading task for cognition. Performance was measured as lateral deviation of the car. Physiological measures included heart rate frequency (HR) and various time- and frequencydomain heart rate variability (HRV) parameters, eye blink frequency and duration. The Borg CR-10 scale was used to evaluate subjective effort and fatigue during the task. Driving control declined over time and was supplemented by HR, HRV, blink frequency and duration, indicating an increase in parasympathetic activity (or a reduction in arousal). An increase in blink frequency was considered as a sign of withdrawal of attentional resources over time. Driving control declined to a greater extent in the large road width group and reflected a lower parasympathetic activity, whereas the inverse was observed for the small road width group. Resource tests reveal a non-specific impairment of information processing following the prolonged drive. However, this was accompanied by an increase in parasympathetic activity. Overall, results indicate that Effort-Regulation Theory better accounts for the impairment of driving control in prolonged driving than does Resource Theory. This suggests that the impact of fatigue is guided more by task goals and intrinsic motivation than by the manner in which the fatigue state developed. Moreover, performance impairment by effort-regulation is dependant more on time on task than on task-demand
Keywords: Automobile driving simulators; Automobile driving -- Psychological aspects; Automobile driving -- Physiological aspects; Traffic accidents; Traffic safety; Fatigue